Observations of pressure anisotropy effects within semi-collisional magnetized plasma bubbles - E. R. Tubman; A. S. Joglekar; A. F. A. Bott; M. Borghesi; B. Coleman; G. Cooper; C. N. Danson; P. Durey; J. M. Foster; P. Graham; G. Gregori; E. T. Gumbrell; et al. (Nature Communications, 2021)
Magnetic fields can be reorganized by plasma flows and lead to effects such as magnetic reconnection. Here the authors explore the evolution of magnetized-plasma bubbles in a semi-collisional regime and the role of pressure anisotropy in influencing the flow of the laser-produced plasma.